2016
DOI: 10.1371/journal.pone.0158070
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prefrontal Activity and Chewing Performance as Function of Wearing Denture in Partially Edentulous Elderly Individuals: Functional Near-Infrared Spectroscopy Study

Abstract: The purpose of this study was to elucidate the effects of wearing a denture on prefrontal activity during chewing performance. We specifically examined that activity in 12 elderly edentulous subjects [63.1±6.1 years old (mean ± SD)] and 12 young healthy controls (22.1±2.3 years old) using functional near-infrared spectroscopy (fNIRS) in order to evaluate the quality of prefrontal functionality during chewing performance under the conditions of wearing a denture and tooth loss, and then compared the findings wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 88 publications
(82 reference statements)
1
45
0
2
Order By: Relevance
“…Other authors, such as Yokoyama et al ,. using near‐infrared spectroscopy, pointed out the relation between mastication and cerebral oxygenation, just as Kamiya et al . reported the effects of dental prostheses on the activity of the PFC during mastication.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Other authors, such as Yokoyama et al ,. using near‐infrared spectroscopy, pointed out the relation between mastication and cerebral oxygenation, just as Kamiya et al . reported the effects of dental prostheses on the activity of the PFC during mastication.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, a greater number of participants are needed to assess the importance of all variables. Activation of cerebral activity was found to increase significantly in the dorsal PFC during chewing while wearing a dental prosthesis, compared with controls without dentures, although experimental studies in animal models suggested that other cerebral zones are activated during mastication, not only the PFC. Furthermore, according to the study by Kamiya et al ., 12 prefrontal activation is not related to age, because little difference was found between elderly participants wearing dentures during mastication and young healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, OD patients did not demonstrate any significant modifications of occlusal state or chewing activities as compared to HC subjects. It has been previously reported that prefrontal activity during chewing is involved in food preference [29], selfevaluation of chewing ability [35,40], food reward [35], food representation, and monitoring of eating behavior [52]. Furthermore, the DLPFC and m-PFC are also involved in multisensory sensory functioning as well as execution, attention, and working memory participations [25][26][27][28][29]32].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to define prefrontal cognitive functioning in regard to food flavor [33], food hardness [34], and sensorimotor generation [35] during chewing. In the present study, we investigated specific behaviors that might be modulated by occlusal contact conditions in OD patients.…”
Section: Introductionmentioning
confidence: 99%